Răspuns :
a=7b
a=b+36
7b=b+36
7b-b=36
6b=36
b=36/6=6
a=7*b=7*6= 42
Si desenul:
a [-----][-----][-----][-----][-----][-----][-----]
b [-----]
\--------------------------------------/
36
a=b+36
7b=b+36
7b-b=36
6b=36
b=36/6=6
a=7*b=7*6= 42
Si desenul:
a [-----][-----][-----][-----][-----][-----][-----]
b [-----]
\--------------------------------------/
36
a=b*7......=> b=a:7
a=b+36...=> b=a-36
a) |__|__|__|__|__|__|__|
b) |__|
\-----------------------/
36
------------------------------------
7b-b=36
b=36:6
b=6
a=7b
a=6*7
a=42
verificare
b=42:7
b=6
a=6+36
a=42
a=b+36...=> b=a-36
a) |__|__|__|__|__|__|__|
b) |__|
\-----------------------/
36
------------------------------------
7b-b=36
b=36:6
b=6
a=7b
a=6*7
a=42
verificare
b=42:7
b=6
a=6+36
a=42